AEROSPACE MANUFACTURING INDUSTRY: A SIMULATION-BASED DECISION SUPPORT FRAMEWORK FOR THE SCHEDULING OF COMPLEX HOIST LINES - Basán, Natalia Paola; Pulido, Raúl; Cóccola, Mariana Evangelina; Méndez, Carlos Alberto (Iberoamerican Journal of Industrial Engineering, 2017)
This paper presents an advanced simulation model for short-term scheduling of complex hoist lines. This problem, generally found in aerospace and electroplating industries, includes several hard constraints that should be considered: single shared hoist, heterogeneous recipes, eventual recycle flows, and no buffers between workstations. Different heuristic-based strategies are incorporated into the computer model in order to improve the solutions generated over time. The aim is to reduce the number of products that must be discarded while minimizing the makespan. In addition, a graphical user interface was developed for quickly evaluating simulated schedules.